Possessing nature : museums, collecting, and scientific culture in early modern Italy - Findlen, Paula (Studies on the history of society and culture, 1994)
In 1500 few Europeans regarded nature as a subject worthy of inquiry. Yet fifty years later the first museums of natural history had appeared in Italy, dedicated to the marvels of nature. Italian patricians, their curiosity fueled by new voyages of exploration and the humanist rediscovery of nature, created vast collections as a means of knowing the world and used this knowledge to their greater glory. Drawing on extensive archives of visitors' books, letters, travel journals, memoirs, and pleas for patronage, Paula Findlen reconstructs the lost social world of Renaissance and Baroque museums.